Pengaruh Whistleblowing system Dan Audit Internal Terhadap Pencegahan Fraud - Ni Kadek Cintia Padma Dewi; I Gusti Ngurah Sanjaya; Partiwi Dwi Astuti (Jurnal Riset Akuntansi Warmadewa, 2025)
This study aims to examine the influence of the whistleblowing system and internal audit on fraud prevention in commercial banks in Bali. The objective of this research is to determine whether the effective implementation of whistleblowing systems and internal audits contributes positively to fraud prevention efforts. The research adopts a quantitative approach, with data collected via questionnaires distributed to regional heads, branch managers, and bank directors from 46 commercial banks in Bali. The collected data are analyzed using multiple linear regression techniques with the aid of SPSS versions 25 to test the research hypotheses. The results indicate that both the whistleblowing system and internal audit have a significantly positive effect on fraud prevention, suggesting that these mechanisms can strengthen internal control systems and enhance the operational transparency of banks. These findings support the fraud triangle theory and provide practical implications for banks to optimize their reporting systems and internal oversight to prevent fraud.